2011
DOI: 10.1002/hipo.20754
|View full text |Cite
|
Sign up to set email alerts
|

BDNF is required for the induction of a presynaptic component of the functional conversion of silent synapses

Abstract: Long‐term potentiation (LTP) has received attention because of its proposed role in learning and memory. Despite substantial effort the pre‐ or postsynaptic expression site of LTP remains unsettled. It has been proposed that LTP is expressed postsynaptically through the functional conversion of “silent synapses.” We had shown that Schaffer collateral (SC) silent and “functional synapses,” which lack and express AMPA receptors, respectively exhibit distinct transmitter release properties. Therefore the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Long-term potentiation (LTP) also develops in the hippocampal-prefrontal pathway after extinction learning occurs (Farinelli et al, 2006), and disrupting this potentiation disrupts fear extinction memory retrieval (Farinelli et al, 2006; Inoue et al, 2013; Judo et al, 2010). Given that BDNF promotes LTP in cortical neurons (Abidin et al, 2007; Cabezas and Buno, 2010; Lu et al, 2010, 2007; Messaoudi et al, 2002), it may simulate fear extinction memory by emulating this neurophysiological plasticity.…”
Section: Bdnf and Extinction Memorymentioning
confidence: 99%
“…Long-term potentiation (LTP) also develops in the hippocampal-prefrontal pathway after extinction learning occurs (Farinelli et al, 2006), and disrupting this potentiation disrupts fear extinction memory retrieval (Farinelli et al, 2006; Inoue et al, 2013; Judo et al, 2010). Given that BDNF promotes LTP in cortical neurons (Abidin et al, 2007; Cabezas and Buno, 2010; Lu et al, 2010, 2007; Messaoudi et al, 2002), it may simulate fear extinction memory by emulating this neurophysiological plasticity.…”
Section: Bdnf and Extinction Memorymentioning
confidence: 99%
“…The basic question as to whether the mechanisms underlying LTP, both the causes and locus of expression, result from changes in presynaptic or postsynaptic function remains contentious, for more details see Bekkers and Stevens (1990), Kullmann and Nicoll (1992), Isaac et al (1995), Liao et al (1995), Bolshakov et al (1997), Debanne et al (1997), Routtenberg (1999), Zakharenko et al (2001), Emptage et al (2003), Martin and Buno (2003), Nicoll (2003), Huang et al (2005), Bayazitov et al (2007), Lauri et al (2007), Fernandez de Sevilla et al (2008), Kerchner and Nicoll (2008), and Cabezas and Buno (2011). For more details about molecular-cellular mechanisms of LTP, readers are referred to several informative reviews published over the course of three decades (Madison and Schuman, 1991; Bliss and Collingridge, 1993; Malenka, 1994, 2003; Roberson et al, 1996; Nicoll and Malenka, 1999; Sanes and Lichtman, 1999; Sweatt, 1999; Bredt and Nicoll, 2003; Malenka and Bear, 2004; Shi et al, 2005; Miyamoto, 2006; Kerchner and Nicoll, 2008; Minichiello, 2009; Li et al, 2010a; Baudry et al, 2011; Kelly et al, 2011a).…”
Section: Cellular/molecular Mechanisms Involved In Ltpmentioning
confidence: 99%
“…),but also promotes presynaptic neurotransmitter release and neuron maturation(Shen et al . ; Cabezas and Buno ). Although it is reported that BDNF exerts its function on synaptogenesis through multiple signaling pathways, leading to cytoskeletal reorganization or gene expression required for synaptogenesis (Waites et al .…”
mentioning
confidence: 96%
“…Brain-derived neurotrophic factor (BDNF) is a wellknown mediator of synapse formation and plasticity (Huang and Reichardt 2003;Luikart and Parada 2006;Lu et al 2008;Yoshii and Constantine-Paton 2010). BDNF not only increases the number of dendritic synapses of hippocampal neurons (Ji et al 2005;Yoshii and Constantine-Paton 2007;Zhou et al 2008a),but also promotes presynaptic neurotransmitter release and neuron maturation (Shen et al 2006;Cabezas and Buno 2011). Although it is reported that BDNF exerts its function on synaptogenesis through multiple signaling pathways, leading to cytoskeletal reorganization or gene expression required for synaptogenesis (Waites et al 2005;McAllister 2007;Sheng and Hoogenraad 2007), the precise mechanisms that link the BDNF to F-actin remodeling in filopodial motility or synapse/spine formation remain unclear.…”
mentioning
confidence: 99%